Theaflavin-3, 3′-Digallate Suppresses RANKL-Induced Osteoclastogenesis and Attenuates Ovariectomy-Induced Bone Loss in Mice - Ai, Zexin; Wu, Yang’ou; Yu, Miao; Li, Jia; Li, Shengjiao (Frontiers in Pharmacology, 2020)
Theaflavin-3, 3′-digallate (TF3) is extracted from black tea and has strong antioxidant capabilities. The aim of this study was to assess the influences of TF3 on osteoclastogenesis and explore the underlying mechanisms. TF3 efficiently decreased receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclast formation and reactive oxygen species (ROS) generation in a dose-dependent manner. Mechanistically, TF3 reduced ROS generation by activating nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream heme oxygenase-1 (HO-1) and also inhibited the mitogen-activated protein kinases (MAPK) pathway. Moreover, micro-computed tomography (CT) analysis, hematoxylin and eosin (H&E) staining, and TRAP staining of the femurs of C57BL/6J female mice showed that TF3 markedly attenuated bone loss and osteoclastogenesis in mice. Immunofluorescence staining, 2′,7′-dichlorofluorescein diacetate (DCFH-DA) staining, and measurement of the levels of malonaldehyde (MDA) and superoxide dismutase (SOD) revealed that TF3 increased the expression of Nrf2 and decreased the intracellular ROS level in vivo. These findings indicated that TF3 may have the potential to treat osteoporosis and bone diseases related to excessive osteoclastogenesis via inhibiting the intracellular ROS level.